Public order policing 2.0: addressing the challenges of the information age - Lee, Ryan (Public Order Policing, 2024)
Most public order policing practitioners focus on the physical space and the immediacy of maintaining order within it and fail to evaluate the role of legitimacy, narrative space and the impacts of the information age, all of which will be discussed within this chapter. It will examine the sophistication of criminal protesters and how communication is leveraged by them. Lastly, it will highlight strategies and tactics for public order professionals to navigate this new and challenging environment.